Wireless Sensor Networks 11th European Conference, EWSN 2014, Oxford, UK, February 17-19, 2014, Proceedings - Krishnamachari, Bhaskar; Murphy, Amy L.; Trigoni, Niki.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book constitutes the refereed proceedings of the 11th European Conference on Wireless Sensor Networks, EWSN 2014, held in Oxford, UK, in February 2014. The 12 revised full papers presented were carefully reviewed and selected from 50 submissions. The papers cover a wide range of topics in the following areas: network protocols, system issues, reliability, and sensing.
Keywords: Computer science; Computer Communication Networks; Software engineering; Computer system performance; Computer software; Computer Science; Computer Communication Networks; Special Purpose and Application-Based Systems; System Performance and Evaluation; Algorithm Analysis and Problem Complexity; Software Engineering; Computation by Abstract Devices